Risk factors for extubation failure in the intensive care unit - Silva-Cruz, Aracely Lizet (2018)
Objective: To determine the risk factors for extubation failure in the intensive care unit. Methods: The present case-control study was conducted in an intensive care unit. Failed extubations were used as cases, while successful extubations were used as controls. Extubation failure was defined as reintubation being required within the first 48 hours of extubation. Results: Out of a total of 956 patients who were admitted to the intensive care unit, 826 were subjected to mechanical ventilation (86%). There were 30 failed extubations and 120 successful extubations. The proportion of failed extubations was 5.32%. The risk factors found for failed extubations were a prolonged length of mechanical ventilation of greater than 7 days (OR = 3.84, 95%CI = 1.01 - 14.56, p = 0.04), time in the intensive care unit (OR = 1.04, 95%CI = 1.00 - 1.09, p = 0.03) and the use of sedatives for longer than 5 days (OR = 4.81, 95%CI = 1.28 - 18.02; p = 0.02). Conclusion: Pediatric patients on mechanical ventilation were at greater risk of failed extubation if they spent more time in the intensive care unit and if they were subjected to prolonged mechanical ventilation (longer than 7 days) or greater amounts of sedative use.